Calcium dysregulation links ALS defective proteins and motor neuron selective vulnerability - Leal, Sónia S.; Gomes, Cláudio M. (Frontiers in Cellular Neuroscience, 2015)
More than 20 distinct gene loci have so far been implicated in amyotrophic lateral sclerosis (ALS), a fatal neurodegenerative disorder characterized by progressive neurodegeneration of motor neurons (MN) and death. Most of this distinct set of ALS-related proteins undergoes toxic deposition specifically in MN for reasons which remain unclear. Here we overview a recent body of evidence indicative that mutations in ALS-related proteins can disrupt fundamental Ca2+ signalling pathways in MN, and that Ca2+ itself impacts both directly or indirectly in many ALS critical proteins and cellular processes that result in MN neurodegeneration. We argue that the inherent vulnerability of MN to dysregulation of intracellular Ca2+ is deeply associated with discriminating pathogenicity and aberrant crosstalk of most of the critical proteins involved in ALS. Overall, Ca2+ deregulation in MN is at the cornerstone of different ALS processes and is likely one of the factors contributing to the selective susceptibility of these cells to this particular neurodegenerative disease.